El fenómeno de la laicidad como elemento identitario: el caso uruguayo = The laicity phenomenon as identity element: the Uruguayan case - Da Costa, Néstor (Civitas - Revista de Ciências Sociais)
This article analyzes the fenomenon of “secularity” in Uruguay. This country has developed a model of secularity that has itself become an issue of identification as well as differentiation in South America. It problematizes the term in its diversity and reviews the historical process from which it originates, considering its main emphasis and the diferent elements of its composition. It identifies the peculiarities of Uruguayan secularity as well as its difficulties